Mortality Rate in the Neonatal Intensive Care Unit at IBN SINA Teaching Hospital Sirte-Libya - Muammar Makhlouf; Intisar Kamal Hassan; Hana Lamen (Sirte Journal of Medical Sciences, 2024)
Studying the mortality rate of newborns in the neonatal intensive care unit (NICU) is of paramount importance as it provides valuable insights into the effectiveness of medical interventions, clinical practices, and healthcare strategies aimed at reducing infant mortality. By analyzing the mortality data, healthcare professionals can identify areas for improvement, implement evidence-based practices, and develop targeted interventions to enhance the quality of care and ultimately save more infant lives, throughout one. Total number of newborns in hospital 4,369 number of death 44. The data focused on death certificates of neonates